Herschel/HerMES: The X-ray-infrared correlation for star-forming galaxies at z~1 - Symeonidis, M.; Georgakakis, A.; Seymour, Nick; Auld, R.; Bock, J.; Brisbin, D.; Buat, V.; Burgarella, D.; Chanial, P.; Clements, D.; Cooray, A.; Eales, S.; et al. (2011)
For the first time, we investigate the X-ray/infrared (IR) correlation for star-forming galaxies (SFGs) at z~ 1, using SPIRE submm data from the recently launched Herschel Space Observatory and deep X-ray data from the 2-Ms Chandra Deep Field-North survey. We examine the X-ray/IR correlation in the soft X-ray (SX; 0.5-2keV) and hard X-ray (HX; 2-10keV) bands by comparing our z~ 1 SPIRE-detected SFGs to equivalently IR-luminous (LIR < 1010 L☉) samples in the local/low-redshift Universe. Our results suggest that the X-ray/IR properties of the SPIRE SFGs are on average similar to those of their local counterparts, as we find no evidence for evolution in the LSX/LIR and LHX/LIR ratios with redshift. We note, however, that at all redshifts, both LSX/LIR and LHX/LIR are strongly dependent on IR luminosity, with luminous and ultraluminous IR galaxies (LIRGs and ULIRGs; LIR < 1011 L☉) having up to an order of magnitude lower values than normal IR galaxies (LIR < 1011 L☉). We derive a LSX-LIR relation and confirm the applicability of an existing LHX-LIR relation for both local and distant LIRGs and ULIRGs, consistent with a scenario where X-ray luminosity is correlated with the star formation rate.